Correlation Method in a ZnO Crystal (2018)
The prediction of vibrational modes of the crystalline molecules or structures based on their properties of symmetry, allow us to use a powerful method to characterize new materials. In this work, the theoret- ical modal analysis was performed by the correlation method, and the optically active Raman vibration modes were obtained for a crystalline system with hexagonal Wurzite type structure. Using the Ramanspectroscopy technique, the Raman Stokes vibration spectrum was obtained for a ZnO crystal. From the theoretical analysis and the experimentally recorded Raman spectrum for ZnO, it was possible toobserve and compare the theoretical method (correlation method) with the experimental method (Raman spectroscopy technique). This analysis suggests that the correlation method is accurate in predicting the modes of vibration of any crystal lattice, which can be used in conjunction with the Raman experimental data in characterizing the crystalline and structural quality of new materials of technological interest.